Modelling the supernova-driven ISM in different environments - Gatto, Andrea; Glover, Simon; Klessen, Ralf S.; Clark, Paul C.; Baczynski, Christian (Monthly notices of the Royal Astronomical Society, 2015)
We use hydrodynamical simulations in a (256 pc)3 periodic box to model the impact of supernova (SN) explosions on the multiphase interstellar medium (ISM) for initial densities n = 0.5-30 cm−3 and SN rates 1-720 Myr−1. We include radiative cooling, diffuse heating, and the formation of molecular gas using a chemical network. The SNe explode either at random positions, at density peaks, or both. We further present a model combining thermal energy for resolved and momentum input for unresolved SNe. Random driving at high SN rates results in hot gas (T ≳ 106 K) filling >90 per cent of the volume. This gas reaches high pressures (104 < P/kB < 107 K cm−3) due to the combination of SN explosions in the hot, low-density medium and confinement in the periodic box. These pressures move the gas from a two-phase equilibrium to the single-phase, cold branch of the cooling curve. The molecular hydrogen dominates the mass (>50 per cent), residing in small, dense clumps. Such a model might resemble the dense ISM in high-redshift galaxies. Peak driving results in huge radiative losses, producing a filamentary ISM with virtually no hot gas, and a small molecular hydrogen mass fraction (≪1 per cent). Varying the ratio of peak to random SNe yields ISM properties in between the two extremes, with a sharp transition for equal contributions. The velocity dispersion in H i remains ≲10 km s−1 in all cases. For peak driving, the velocity dispersion in Hα can be as high as 70 km s−1 due to the contribution from young, embedded SN remnants.
Gesehen am 09.08.2021